2021
DOI: 10.1053/j.gastro.2021.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Liver Enzymes, Ferritin, C-reactive Protein, D-dimer, and Age Are Predictive Markers of Outcomes Among African American and Hispanic Patients With Coronavirus Disease 2019

Abstract: S evere acute respiratory syndrome coronavirus 2 caused a worldwide outbreak. Its associated disease, coronaviruses disease 2019 (COVID-19), causes respiratory, gastrointestinal (GI), inflammatory, and neurologic symptoms. 1 In the United States, minorities such as African Americans (AA) and Hispanics (HSP) have shown a higher incidence of the disease. 2,3 . However, no detailed characterization of the disease's features in these populations has been performed. 4 Although the initial focus was on saving lives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…The United States is one of the most ethnically and racially diverse countries in the world encompassing 13.4% African Americans (AA) and 18.5% Latinos/Latinas (LAT) [1]. Disparities among various ethnic groups span many aspects of health [2][3][4], and specific racial/ethnic minority populations have been disproportionately affected by the morbidity and mortality related to COVID-19 [5][6][7]. Reports across the US indicate that African American and Hispanic populations have higher COVID-19 related hospitalization and mortality than Caucasians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The United States is one of the most ethnically and racially diverse countries in the world encompassing 13.4% African Americans (AA) and 18.5% Latinos/Latinas (LAT) [1]. Disparities among various ethnic groups span many aspects of health [2][3][4], and specific racial/ethnic minority populations have been disproportionately affected by the morbidity and mortality related to COVID-19 [5][6][7]. Reports across the US indicate that African American and Hispanic populations have higher COVID-19 related hospitalization and mortality than Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the AA and LAT are essential workers/ frontline workers who need to work in person and are at even higher risk of contracting COVID-19. There may also be differences in the provisions of hospital care by racial/ethnic groups [4,12], but there has not been adequate data on hospital outcomes by race or ethnicity that adjusts for potential confounders. Four major reasons may explain the higher risk for COVID-19, Age, co-morbidities (such as diabetes, obesity, hypertension, cardiovascular Asthma, chronic obstructive pulmonary disease (COPD), and chronic kidney disease), access to health care and social economic status particularly for minority [4,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in another recent study CRP and transaminases emerged as risk factors of mortality in COVID-19 hospitalized patients. 33 Since CRP is elevated in most inflammatory conditions, so as pneumonia 34 , its prognostic role need to be carefully weighted. Indeed, with such awareness, regular monitoring of CRP values during hospitalization should be carried out in relation to clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a large dataset from Chile, reported [ 20 ] that diarrhea was present in 7.3%, and abdominal pain in 3.7% in a cohort of 7,016 patients. In the US which is the country with most positive confirmed cases in the world, Ashktorab et al [ 21 ] reported that in 447 patients with a majority of them being African Americans, diarrhea was predominant in 19.45%, abdominal pain present in 15.8%. African Americans had the highest diarrhea prevalence of 22.4%.…”
Section: Gi Symptoms and Comorbidities In Covid-19 Outcomementioning
confidence: 99%